2013
DOI: 10.1038/modpathol.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Integration of KRAS testing in the diagnosis of pancreatic cystic lesions: a clinical experience of 618 pancreatic cysts

Abstract: With improvements in abdominal imaging, detection of incidental pancreatic cysts are becoming increasingly common. Analysis of pancreatic cyst fluid from fine-needle aspiration is particularly important in identifying intraductal papillary mucinous neoplasms (IPMNs) and mucinous cystic neoplasms (MCNs), which have significant implications in clinical intervention and follow-up. Previous controlled studies have shown that KRAS mutations in cyst fluid are highly specific for mucinous differentiation in pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 21 publications
5
99
0
1
Order By: Relevance
“…38 However, a recent study indicated KRAS mutations have a sensitivity of 14% detecting MCN lesions, which is significantly lower than its IPMN counterpart. 27 This finding was replicated again in 2014 where only 1/16 patients (6%) had a positive KRAS mutation in an MCN population. Multiple studies have ruled out GNAS as a potential marker for MCNs as this mutation has only been found in IPMN lesions.…”
Section: Mucinous Cystic Neoplasmsupporting
confidence: 65%
See 1 more Smart Citation
“…38 However, a recent study indicated KRAS mutations have a sensitivity of 14% detecting MCN lesions, which is significantly lower than its IPMN counterpart. 27 This finding was replicated again in 2014 where only 1/16 patients (6%) had a positive KRAS mutation in an MCN population. Multiple studies have ruled out GNAS as a potential marker for MCNs as this mutation has only been found in IPMN lesions.…”
Section: Mucinous Cystic Neoplasmsupporting
confidence: 65%
“…24 Various studies have shown that KRAS has excellent specificity (ranging from 96%-100%), but has limited sensitivity (ranging from 45%-65%) in detecting mucinous neoplasms. [25][26][27] When combining CEA and KRAS, one study noted an increase in identification in pre-malignant and malignant cysts. 26 On the other hand, GNAS causes downstream production of cAMP that ultimately results in uncontrolled growth.…”
Section: Intraductal Papillary Mucinous Neoplasmmentioning
confidence: 99%
“…Interestingly, the frequency of mutated KRAS remains consistent as IPMN progresses (i.e., from adenoma to carcinoma) [13]. However, KRAS mutations have been shown to have high specificity, but low sensitivity for mucinous differentiation (100-96% and 54-45%, respectively) [14,15].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…Pancreatic cyst fluids tested obtained by EUS-FNA were consecutively accrued for routine KRAS mutational analysis between January 2006 and December 2013 at the University of Pittsburgh Medical Center (Pittsburgh, PA; ref. 7). In all cases, cyst fluid was submitted for molecular analysis by the endoscopist because of uncertainty as to whether a pancreatic cyst represented a cystic neoplasm.…”
Section: Casesmentioning
confidence: 99%
“…Previously, we reported the results of our institution's clinical experience with DNA testing for KRAS mutations from pancreatic cyst fluid obtained by EUS-FNA (7). KRAS mutations had a specificity of 100% but a sensitivity of 54% for mucinous differentiation.…”
Section: Introductionmentioning
confidence: 99%